2016
DOI: 10.1159/000445770
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Neutrophil Extracellular Traps in Shiga Toxin-Associated Hemolytic Uremic Syndrome

Abstract: Hemolytic uremic syndrome (HUS), a vascular disease characterized by hemolytic anemia, thrombocytopenia, and acute renal failure, is caused by enterohemorrhagic Shiga toxin (Stx)-producing bacteria, which mainly affect children. Besides Stx, the inflammatory response mediated by neutrophils (PMN) is essential to HUS evolution. PMN can release neutrophil extracellular traps (NET) composed of DNA, histones, and other proteins. Since NET are involved in infectious and inflammatory diseases, the aim of this work w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 40 publications
5
50
0
Order By: Relevance
“…These observations in combination with recent reports of a decreased degradation of neutrophil extracellular traps (NETs) in TMA [10] and increased formation of NETs [11] have suggested a role for NETs in thrombotic microangiopathic disorders. NETs consist of decondensed chromatin covered with antimicrobial proteins/peptides and are released from mainly activated neutrophils in a ROS/NADPH-dependent manner [12,13] .…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…These observations in combination with recent reports of a decreased degradation of neutrophil extracellular traps (NETs) in TMA [10] and increased formation of NETs [11] have suggested a role for NETs in thrombotic microangiopathic disorders. NETs consist of decondensed chromatin covered with antimicrobial proteins/peptides and are released from mainly activated neutrophils in a ROS/NADPH-dependent manner [12,13] .…”
Section: Introductionmentioning
confidence: 62%
“…Globular actin in the presence of ATP can inhibit DNase-I [23] , potentially presenting a mechanism for how tissue damage that releases ATP and actin can prevent NET degradation during infections. It was recently shown that neutrophils from Stx-associated HUS patients are more likely to produce NETs [11] , and it is therefore tempting to speculate that the decreased NET degradation which we observed in STEC-HUS may be part of the acute response to fight the infection. As a consequence, increased NET release in combination with attenuated degradation may adversely contribute to some of the kidney damage in STEC-HUS through STEC-independent mechanisms such as the pro-thrombotic properties of NETs [24] .…”
Section: Discussionmentioning
confidence: 81%
“…Along with other NET articles published in the Journal of Innate Immunity [24][25][26] , these studies emphasize the importance of neutrophils and extracellular traps in the early immune response to an invading pathogen. Together with the other contributions in the first 2017 issue, this collection of articles covers a number of essential scientific problems within the field of innate immunity that should be of great interest to our readers.…”
mentioning
confidence: 76%
“…It is more than obvious that this chapter has not yet been closed since many researchers are still contributing to it. It was first believed that NETs play an important role in immobilizing bacterial pathogens, but evidence is now accumulating that they are also involved in many other processes, such as the induction of inflammatory reactions [2,3]. Moreover, NETs can promote immunothrombotic processes since they activate the coagulation system [4].…”
Section: Going Fishingmentioning
confidence: 99%